Cabazitaxel suppresses colorectal cancer cell growth via enhancing the p53 antitumor pathway. Issue 11 (11th October 2021) - Zhang, Wen; Sun, Ruiqian; Zhang, Yongjun; Hu, Rong; Li, Qian; Wu, Weili; Cao, Xinyu; Zhou, Jiajian; Pei, Jianfeng; Yuan, Ping
Abstract : There were approximately 1.93 million new cases and 940 000 deaths from colorectal cancer in 2020. The first‐line chemotherapeutic drugs for colorectal cancer are mainly based on 5‐fluorouracil, although the use of these drugs is limited by the development of drug resistance. Consequently, there is a need for novel chemotherapeutic drugs for the efficient treatment of colorectal cancer patients. In the present study, we screened 160 drugs approved by the Food and Drug Administration and identified that cabazitaxel (CBT), a microtube inhibitor, can suppress colony formation and cell migration of colorectal cancer cells in vitro . CBT also induces G2/M phase arrest and apoptosis of colorectal cancer cells. Most importantly, it inhibits the growth of colorectal cancer cell xenograft tumors in vivo . Transcriptome analysis by RNA‐sequencing revealed that Tub family genes are abnormally expressed in CBT‐treated colorectal cancer cells. The expression of several p53 downstream genes that are associated with cell cycle arrest, apoptosis, and inhibition of angiogenesis and metastasis is induced by CBT in colorectal cancer cells. Overall, our results suggests that CBT suppresses colorectal cancer by upregulating the p53 pathway, and thus CBT may have potential as an alternative chemotherapeutic drug for colorectal cancer. Abstract : In the present study, we screened 160 drugs approved by the Food and Drug Administration, aiming to identify novel chemotherapeutic agents for colorectal cancer (CRC) treatment. We identified that the microtubule inhibitor cabazitaxel (CBT) has a suppressive effect on CRC cells both in vitro and in vivo . Transcriptome analysis revealed that CBT induced apoptosis in CRC cells by upregulating the p53 pathway, implying that CBT may hold chemotherapeutic potential for the treatment of patients with CRC.